Boosting the therapeutic efficiency of nanovectors: exocytosis engineering. Issue 11 (6th March 2017) - Corvaglia, Stefania; Guarnieri, Daniela; Pompa, Pier Paolo
Abstract : A novel strategy, named "exocytosis engineering", enables a strong increase of the therapeutic efficiency of mesoporous silica nanocarriers. Abstract : In this work, we developed a new general strategy, which we named "exocytosis engineering", to strongly increase the intracellular persistence of nanocarriers and thus the effective dose of transported drugs. The strategy is based on the co-loading of a drug and an exocytosis inhibitor in the nanocarrier, to hinder the high tendency of cells to remove internalized nanocarriers, limiting the pharmacological efficiency of the nanoformulation. In particular, by using a well-known chemotherapeutic drug (doxorubicin) and an efficient exocytosis inhibitor (dimethilamyloride) co-loaded in mesoporous silica nanocarriers, we demonstrated a >6-fold increase in the intracellular dose of the drug (for the same administered dose), achieving a great improvement in its therapeutic action. A strong gain in the cytotoxic effect of the drug was, in fact, observed both in several tumor cell lines and in 3D tumor spheroids. The proposed approach is versatile and broadly applicable to several classes of nanocarriers and drugs, thus opening a fascinating outlook in nanomedicine.